Welfare Conditionality and Social Identity Effect Mechanisms and the Case of Immigrant Support - Lena von Deylen; Philipp C. Wichardt (Social Sciences)
The present paper discusses the effects of social identity and self-determination theory and highlights their relevance for welfare conditionality with respect to individual behaviour and well-being. While welfare conditionality may provide economic incentives for certain desired behaviours, e.g., active job search, it is argued that their impact on the claimants’ social self-construal and identity may offset potentially positive effects and increase, for example, social segregation. Taking the integration of immigrants, one of the biggest contemporary challenges for many societies, as a leading example, possible negative effects of welfare conditionality are highlighted and contrasted with the imposed economic incentives. Weighing benefits and potential risks, it is argued that the excessive use of welfare conditionality is likely to backfire in the long run and that this should be taken into account by policy makers. Moreover, it is argued how similar effects can be expected to arise also in different contexts such as the support of child parenting by singles.